2014
DOI: 10.5578/mb.7796
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Beta-Lactamase-Associated Resistance in Acinetobacter baumannii Strains Isolated from Clinical Samples

Abstract: * Bu çalışma, Ankara Üniversitesi Araştırma Fonu tarafından 12B3330006 proje numarasıyla desteklenmiş ve 2. KlinikMikrobiyoloji Kongresi (9-13 Kasım 2013, Belek, Antalya)'nde poster olarak sunulmuştur. ÖZETAcinetobacter baumannii hastanelerde, özellikle yoğun bakım ünitelerinde mortalite ve morbiditeyi artıran, hastane kaynaklı enfeksiyonların önemli bir nedenidir. Bu çalışmanın amacı, klinik örneklerden izole edilen A.baumannii suşlarının antibiyotik duyarlılıklarını, direnç genlerini ve izolatların birbirler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…According to studies carried out in adults in our country, OXA-48 is the most frequently found carbapenemase of the Enterobacteriaceae family and IMP and NDM-1 enzymes have also been confirmed in K.pneumoniaea (16,17). The most commonly isolated resistance enzyme in A, baumanii isolates is OXA-23, which is followed respectively by OXA-58, OXA-24 and GES (18)(19)(20). Iraz et al have detected VIM and GES enzymes in the P. aeruginosa isolate resistant to 23 carbapenems (21).…”
Section: The Distribution Of Carbapenemasesmentioning
confidence: 89%
“…According to studies carried out in adults in our country, OXA-48 is the most frequently found carbapenemase of the Enterobacteriaceae family and IMP and NDM-1 enzymes have also been confirmed in K.pneumoniaea (16,17). The most commonly isolated resistance enzyme in A, baumanii isolates is OXA-23, which is followed respectively by OXA-58, OXA-24 and GES (18)(19)(20). Iraz et al have detected VIM and GES enzymes in the P. aeruginosa isolate resistant to 23 carbapenems (21).…”
Section: The Distribution Of Carbapenemasesmentioning
confidence: 89%
“…21 , 25 Li et al, 7 reported 33 different PFGE patterns for 145 carbapenem resistant A. baumannii isolates and detected 8 different PFGE clones. Keskin et al, 19 studied a group of 201 Acinetobacter spp . isolates and found they could be categorized into 4 dominant genotypes (A, B, C, and D).…”
Section: Discussionmentioning
confidence: 99%
“…For OXA-type carbapenemase screening, primers targeting the OXA-23, OXA-24, OXA-51, and OXA-58 gene regions were used in multiplex PCRs. 19 , 20 The primers and estimated PCR DNA segment sizes are shown in ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Çalışmamızda, A. baumannii ve P. aeruginosa suşlarında kolistin duyarlılık oranlarının sırasıyla %97 ve %97.4 olduğu görülmüştür. Yurt içinde yapılmış çeşitli çalışmalarda, A. baumannii suşlarında kolistin duyarlılığının %94-100 oranlarında saptandığı, P. aeruginosa suşlarında ise bu oranın %98-100 olduğu görülmüştür (3,(8)(9)(10)(11)(12)(13)(14) . Yurt dışında yapılan çeşitli çalışmalarda, A. baumannii suşlarında kolistin direncinin İspanya'da %40.7, Kore'de %30.6 ve Amerika Birleşik Devletleri'nde %2.1 olduğu görülmüştür (15)(16)(17) .…”
Section: Pseudomonas Aeruginosa N = 77unclassified